Ontological plurality (Maps, Levels and Concepts) with no fragmentation of meaning (life-world, metaphors and networks) - Espinosa, Luciano (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The fundamental complexity of ontological plurality demands to be understood with fresh concepts and metaphors: on the one hand, they have to overcome the inner compartmentalization, but on the other hand, they have to build bridges of meaning for the sake of a more integrative approach of the reality. The fragmentation should be avoided, both from an objective perspective and a subjective one, respectively, through the creation of open classifications and indirect symbolic links that may compensate the disciplinary specialization. Notions such as level, map, life-world and network contribute to this task.
Keywords: ontology; concept; metaphor; life-world; map; level; network